Design and analysis of construction and recombination module using Idury Waterman Algorithm for fragment assembly application / Hafifi Mohd Rafi - Mohd Rafi, Hafifi (2012)
There is several algorithms use in sequencing of DNA fragment. This paper presents a study on design and analysis of construction and recombination module using IduryWaterman algorithm and fragment assembly application using Verilog. This algorithm will be implemented on the Xilinx ISE 12.4 software to model the sequence and optimize the last sequence of DNA. The DNA sequences will be overlapped in every fragment. Combination of Eulerian path and de Bruijn graph concept will guide the overlaps process between the DNA sequences. Step by step on how the fragment move and overlap to each other. The result of the proposed algorithm, verifies the validity of proposed algorithm.